PERAN CREATIVE DESIGN & CONTENT PLANNER DALAM STRATEGI BRANDING “COOL ENOUGH” UNTUK PENINGKATAN BRAND AWARENESS DAN BRAND ASSOCIATION DI SMOOLY SEMARANG - Nabila Nur Khotimah; Muhammad Bayu Widagdo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This research is motivated by the low level of brand awareness and brand association of Smooly, a healthy beverage brand in Semarang. Based on a survey of 200 respondents, only 30.5% were aware of the brand, and most did not understand its value as a healthy lifestyle brand. This indicates that Smooly’s communication strategy, particularly through social media, has not been optimal. This study aims to improve brand awareness and brand association through the “Cool Enough” campaign using social media management and event management strategies. The research applies Brand Equity, Brand Communication, and AISAS model as theoretical frameworks. The campaign was conducted for six weeks through Instagram, TikTok, and the “Smooly Health and Move Fest” event. The author acted as Creative Design and Content Planner responsible for visual design and content planning. The results show an increase in Instagram followers from 4,951 to 5,157, production of 20 Instagram contents and 10 TikTok videos, and an offline event attended by approximately 50 participants. These findings indicate that the campaign successfully increased brand exposure and audience engagement.